Pleasantness emotions and neural activity induced by the multimodal crispiness of monaka ice cream - Yamamoto, Takayuki; Tanaka, Ryo; Kochiyama, Takanori; Nota, Yukiko; Tsuchiya, Hitomi; Kawamoto, Masato; Sato, Wataru (Frontiers in Nutrition, 2025)
Monaka ice cream is a frozen confection consisting of ice cream sandwiched between two wafers. Previous psychological research has reported that monaka ice cream with a relatively low moisture content delivers crispiness and enhances positive emotions during consumption. However, the neural basis of these subjective impressions remains unclear. Therefore, this study aimed to investigate the neural mechanisms through which crispy monaka ice cream evokes pleasurable emotions. Ten healthy adults participated in the study. The participants first consumed two types of monaka ice cream (low moisture content, approximately 7%; and high moisture content, approximately 12%) in random order. The consumption method involved breaking the ice cream in half by hand and eating three bites per video samples. Subsequently, we performed functional magnetic resonance imaging (fMRI) while the participants watched multimodal (visual + auditory) videos of the low- and high-moisture-content monaka ice cream, recalling their eating experiences. During fMRI image acquisition, the participants rated their preference levels on a four-point scale. Preference ratings were higher for low-moisture-content monaka ice cream than for high-moisture-content cream. Lower moisture contents elicited stronger activity in the bilateral auditory cortex and bilateral ventromedial prefrontal cortex (vmPFC) compared with the high moisture content condition. Additionally, preference ratings were positively correlated with vmPFC activity. These findings suggest that the multimodal processing of crispy monaka ice cream involves activity in the auditory cortex and vmPFC, the latter of which contributes to the generation of subjective pleasurable emotions.